2022
DOI: 10.21037/apm-22-903
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the causes of failed placement of nasoenteric tube under DSA guidance and treatment strategies for successful re-catheterization

Abstract: Background: For patients with advanced cancer or patients who have undergone digestive tract reconstruction, enteral nutrition is the most important nutritional support therapy, which can reduce the risk of enteral infection and improve self-immunity; while digital subtraction angiography (DSA) guided nasoenteric tube placement is suitable for nutritional support and palliative treatment of most patients with advanced cancer, many doctors because the preoperative preparation is not sufficient or the intraopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is presumed that abdominal surgery history might change the shape of digestive organs, block the pass of the tube, and eventually result in the failure of tube placement. More specifically, pyloric stenosis, obstruction of the gastric sinus, and other structural factors are the most common reasons for the failure of placement 38 . A previous study also suggested that a history of upper gastrointestinal surgery history might undermine the success of fluoroscopy‐guided placement of nasoenteral tubes, 39 which can also be explained by the assumption mentioned above.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is presumed that abdominal surgery history might change the shape of digestive organs, block the pass of the tube, and eventually result in the failure of tube placement. More specifically, pyloric stenosis, obstruction of the gastric sinus, and other structural factors are the most common reasons for the failure of placement 38 . A previous study also suggested that a history of upper gastrointestinal surgery history might undermine the success of fluoroscopy‐guided placement of nasoenteral tubes, 39 which can also be explained by the assumption mentioned above.…”
Section: Discussionmentioning
confidence: 98%
“…More specifically, pyloric stenosis, obstruction of the gastric sinus, and other structural factors are the most common reasons for the failure of placement. 38 A previous study also suggested that a history of upper gastrointestinal surgery history might undermine the success of fluoroscopy-guided placement of nasoenteral tubes, 39 which can also be explained by the assumption mentioned above. Besides this, the study mentioned above also showed that normal peristalsis of the upper gastrointestinal tract can promote the success of placement.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of other magnetic objects in the vicinity of the patient, such as medical equipment or jewelry, can interfere with the magnetic tip guidance process and lead to inaccurate placement of the feeding tube ( 41 ). The use of a guidewire increases the risk of infection, as it can introduce bacteria or other pathogens into the gastrointestinal tract ( 42 ).…”
Section: Introductionmentioning
confidence: 99%